Carbon stocks in shaded Theobroma cacao farms and adjacent secondary forests of similar age in Cameroon - Norgrove, L.; Hauser, S. (2013)
Cacao is an important smallholder crop in West Africa, often grown under a forest canopy. Yields from cacao farms are low so farmers consider removing shade trees, however, the impacts on pest and disease dynamics, soil fertility and thus yield in the longer term are not understood. We estimated carbon stocks in shaded cacao systems in Cameroon using equations that took account of wood densities of individual species. The average C stock in cacao trees was 14.4 Mg C ha-1, compared with 121.1 Mg C ha-1 in the upper shade tree canopy, 5.8 Mg C ha-1 in necromass and 90 Mg ha-1 in soil. While total stock was comparable to that in secondary forest, only a small proportion was in the cacao per-se. Cutting shade trees would significantly reduce carbon stocks. Impacts of reduced C stock on sustainability are discussed